Obstructive Sleep Apnea Syndrome in Pediatric Age Group - Gülçin Benbir; Derya Karadeniz (Türk Uyku Tıbbı Dergisi, 2014)
Obstructive sleep apnea syndrome (OSAS) is divided into two categories; in adults and in children. Although its exact incidence in pediatric age group is not well-known, it is suggested as occurring in approximately 1% of young children. Although advanced age is a very important risk factor for OSAS, some amongst the predisposing factors for OSAS in children are male gender, obesity (above 85th percentile; body mass index >25 kg/m2), hypothyroidism or other endocrine disorders, craniofacial abnormalities and the family history of OSAS in-first degree relatives (2-8 times). Nonrestorative sleep, frequent body movements during sleep and sweating especially in the neck and chest area, are the symptoms observed in almost half of the patients. Nocturia may manifest itself as nocturnal enuresis in the pediatric age group. Gastroesophageal reflux and open mouth saliva drooling during sleep are also commonly encountered in children with OSAS. OSAS is also an important risk factor for cardiovascular diseases in the pediatric age group. Increased blood pressure, sympathetic and parasympathetic nervous system activities and noradrenalin levels are reported to be common in children with OSAS. It should be noted by the physicians that even in youngl age, sleep apnea is associated with increased nocturnal sympathetic activity, and therefore cause of secondary cardiovascular complications. Surgical intervention is more commonly suggested in the treatment of OSAS in pediatric age group and constitutes first-line therapy together with positive airway pressure therapy.